IMPLEMENTASI PENJAMINAN MUTU MADRASAH - Ari Prayoga; Azhar Lujjatul Widad; Elin Marliana; Ima Siti Mukarromah; Uus Ruswandi (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2019)
Quality control in the management of education is faced with constraints of limited educational resources. Therefore we need an effort to control quality in the form of guarantees, so that all aspects related to education services provided are in accordance with or exceeding national education standards. This paper aims to describe the implementation of education quality assurance in Madrasah Aliyah An-Najiyah Bandung, including; implementation of madrasah quality assurance, quality implementation obstacles, and solutions in overcoming obstacles to implementing quality assurance in Madrasah aliyah An-Najiyah Bandung. This research uses a qualitative approach through descriptive methods. The data collection techniques using in-depth interviews, observation, and literature study. The results showed that; first, In terms of quality assurance in terms of the eight national education standards in Madrasah Aliyah An-Najiyah, Bandung, it is at a good standard level and even exceeds the minimum service standard so that it becomes a distinct advantage for this madrasa. High competitive power makes the process of implementing quality assurance more stringent. Second, the internal obstacle that arises is the absence of a special quality assurance institution internal to the institution that controls all aspects of quality assurance. Third, the solution to the obstacles that arise will be minimized if institutionally already built.